A Marxist Feminist Reading of Patriarchy and Capitalism in Joe Wright’s Pride and Prejudice (2005): A Feminist Literature Analysis - Asih, Ida Ayu Hari; Putra, Galuh Febri; Matradewi, Ni Ketut Widhiarcani; Simonin, Thibault (Journal of Language and Literature Studies, 2025)
This study investigates the types of oppression that women face, as represented in Pride and Prejudice (2005), with a particular emphasis on how patriarchal and capitalist systems prevent female autonomy. The analysis, which draws on Marxist Feminist theory by Heidi Hartmann, investigates how marriage, class, and gender norms function as mechanisms of structural control. Utilizing a documentation strategy that includes repeated film viewings and scene annotations, the study employs thematic qualitative analysis to discover repeating patterns of commodification, patriarchal control, and feminist resistance. Key sequences featuring Elizabeth Bennet, Charlotte Lucas, and Lady Catherine de Bourgh are studied critically to demonstrate varied female reactions to intersecting power structures. The findings reveal that female characters are systematically subjected to societal constraints founded in both patriarchy and capitalism, with many being positioned as commodities in a marriage market dominated by class and gender expectations. Notably, Elizabeth Bennet emerges as a symbol of resistance, confronting these overlapping forms of oppression with her assertiveness and rejection of transactional marriage. This study contributes to feminist film analysis by examining how period dramas reflect and replicate historical gender beliefs. Furthermore, it has instructional value in raising awareness of how contemporary forms of gender-based oppression may develop in subtler ways over time. As the media continues to impact public consciousness, understanding the linkages of patriarchy and capitalism in cultural texts fosters critical thinking and promotes gender justice through education.